Polydopamine nanoparticles as immunomodulators: inhibition of M1 microglial polarization - Ceccarelli, Maria Cristina; Lai, Luigi; Carmignani, Alessio; Battaglini, Matteo; Ciofani, Gianni (Frontiers in Bioengineering and Biotechnology, 2025)
Neuroinflammation is a central feature of numerous neurodegenerative diseases, including Alzheimer’s and Parkinson’s disease, where excessive activation of microglia can contribute to neuronal damage. The pro-inflammatory M1 phenotype of microglia is characterized by increased production of reactive oxygen species (ROS), overexpression of surface markers such as CD40 and CD86, and secretion of cytokines like IL-6, IL-8, and TNF-α, all of which exacerbate oxidative stress and neurodegeneration. The development of strategies to control and tune microglial pro-inflammatory activation is therefore critical for reducing the progression of these conditions. In this study, the potential of polydopamine nanoparticles (PDNPs) as novel immunomodulatory agents for attenuating M1 microglial polarization was investigated. PDNPs were synthesized via a simple and reproducible protocol and thoroughly characterized in terms of size, morphology, hydrodynamic diameter, and surface charge, confirming their uniformity and stability. Biocompatibility assays showed that PDNPs are well tolerated by human microglial clone 3 (HMC3) cells, with minimal cytotoxicity even at relatively high concentrations. Confocal microscopy and flow cytometry analyses demonstrated efficient internalization of PDNPs by microglia, with preferential accumulation in lysosomal compartments and negligible mitochondrial localization. To mimic neuroinflammatory conditions, HMC3 cells were stimulated with interferon-gamma (IFN-γ), which significantly increased intracellular ROS levels, surface expression of CD40 and CD86, and secretion of pro-inflammatory cytokines. The co-treatment with PDNPs effectively mitigated these effects by reducing oxidative stress, suppressing the upregulation of M1 markers, and decreasing cytokine release, thereby preventing the shift toward a pro-inflammatory state. The results of this work demonstrate that PDNPs not only exhibit excellent biocompatibility and cellular uptake but also provide a robust means of counteracting IFN-induced microglial activation. These results establish PDNPs as promising nanoplatforms for modulating neuroinflammation and microglial activation. This study highlights the potential of PDNPs for future applications in the treatment of neurodegenerative diseases.